Hayes, Hollister, and Kelman families papers - Ambler, Barbara Hayes, 1926-2006.; Hayes, Barbara Monteath Kelman, 1893-1975.; Hayes, David, 1832-1865.; Hayes, John David, 1888-1957.; Hayes, Margaret Young, 1857-1949.; Hayes, W. M. (Watson M.), 1857-1944.; Hollister, Margaret Hayes, 1917-; Kelman, John, 1864-1929.
Correspondence, diaries, lectures, sermons, memoirs, genealogical material, and printed matter pertaining chiefly to members of the Hayes family and their careers as Presbyterian missionaries and educators in China. Includes papers of Margaret Hayes Hollister; her parents, Barbara Monteath Kelman Hayes and John David Hayes; her paternal grandparents, Margaret Young Hayes and W.M. Hayes; her maternal grandfather, John Kelman; and her paternal great-grandfather, David Hayes.
Correspondence primarily of W.M. Hayes and Margaret Young Hayes to family members and to the Presbyterian Church in Swarthmore, Pa., pertaining to their years in China. Topics include the first Sino-Japanese War, 1894-1895; the 1911 plague in China; the Chinese Revolution, 1911-1912; and the second Sino-Japanese War, 1937-1945. Also includes correspondence of Barbara Monteath Kelman Hayes and other family members.
Includes a diary kept by W.M. Hayes while interned by the Japanese in the Weihsien Civilian Assembly Center, Shandong Sheng, China, 1943-1944; papers of his granddaughter, Barbara Hayes Ambler, concerning her internment in the Philippines, 1941-1943, and her voyage on the ocean liner Gripsholm as part of a Japanese-American civilian prisoner exchange during World War II; pocket diaries of Barbara Monteath Kelman Hayes relating chiefly to her later years in the United States; sermons by her father, John Kelman, as well as a journal and lecture describing his voyage from Australia on the steamship Oroya, 1888, and his years in Australia; papers of Margaret Hayes Hollister concerning her early life in China, student years at Yanjing da xue (Yenching University) in Peking, China, and career as a social worker in Washington, D.C.; material pertaining to John David Hayes's years as a student in China and at Oxford University and as a prisoner of the Chinese Communists in 1951 and 1952; and letters of David Hayes written during his Civil War service with the 100th Pennsylvania Infantry Regiment.
Library of Congress Prints and Photographs Division.
Collection material in English, with Chinese.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Hayes family; Hollister family; Kelman family; United States. -- Army. -- Pennsylvania Infantry Regiment, 100th (1861-1865); Gripsholm (Ocean liner); Oroya (Steamship); Oxford University -- Students; Yanjing da xue -- Students; Weihsien Civilian Assembly Center; Americans -- China; Education -- China; Missions -- China; Plague -- China; Political prisoners -- China; Presbyterian Church -- Missions -- China; Sino-Japanese War, 1894-1895.; Sino-Japanese War, 1937-1945.; Social service -- Washington (D.C.); Voyages and travels; World War, 1939-1945 -- Concentration camps -- China -- Shandong Sheng; World War, 1939-1945 -- Concentration camps -- Philippines; World War, 1939-1945 -- Prisoners and prisons, American; World War, 1939-1945 -- Prisoners and prisons, Japanese; World War, 1939-1945 -- China; Australia -- Description and travel; China -- History -- 1861-1912.; China -- History -- Revolution, 1911-1912.; China -- History -- Republic, 1912-1949.; China -- Social life and customs; Pennsylvania -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.